Metabolic Adjustments following Glutaminase Inhibition by CB-839 in Glioblastoma Cell Lines - De los Santos-Jiménez, Juan; Rosales, Tracy; Ko, Bookyung; Campos-Sandoval, José Ángel; Alonso-Carrión, Francisco José; Márquez-Gómez, Javier; DeBerardinis, Ralph J; Mates-Sánchez, José Manuel (IOAP-MDPI, 2023)
Glioblastoma multiforme is the most common primary brain tumor. Unfortunately, it is also one of the cancer types that has the worst morbidity and mortality ratios, so new targets and treatments need to be found. The metabolism of glutamine is fundamental for the proliferation of many tumor cells, including glioblastomas. Glutaminase isoenzyme GLS is one of the responsible enzymes for the pro-oncogenic pathways that induce metabolic reprogramming and leads to altered levels of some amino acids and other key intermediary metabolites in glioblastoma. Using the clinically approved GLS inhibitor CB-839 (Telaglenastat), we found significant changes in glutamine metabolism, including both the oxidative and reductive fates of Gln-derived alpha-ketoglutarate in the tricarboxylic acid cycle, in three glioblastoma cell lines. One of them, the T98G glioblastoma cell line, showed the greatest modification of metabolite levels involved in the de novo biosynthetic pathways for nucleotides, as well as a higher content of methylated and acetylated metabolites.
Keywords: Cancer; Aspartate; Cancer; Cancer metabolism; CB-839; Citrate; Glioblastoma; Glutaminase; Glutamine; Metabolic reprogramming; Metabolomics